Perancangan Pendampingan “Remaja Bestie Ibu Hamil” Dalam Upaya Peningkatan Kesehatan Ibu Hamil Saat Pandemi - Etty Nurkhayati; Nani Yunarsih; Refi Lindawati (Jurnal Pelayanan dan Pengabdian Masyarakat Indonesia, 2024)
Remaja Posyandu is a health service initiative aimed at providing information and skills to adolescents related to pregnancy. In the context of the COVID-19 pandemic, health activities, including antenatal examinations, have been restricted. This article discusses community service activities in the remaja Posyandu, with a focus on providing preparation to adolescents regarding pregnancy. The approach used is an educative persuasive approach with the hope of changing adolescent behavior to support pregnant women, especially during the pandemic. The research was conducted in Gelam Village, Banten Girang Subdistrict, and received a positive response from the community, especially adolescents. The material presented was well-received, as evidenced by the increase in adolescent knowledge after the activity. The pretest results showed that 45% of adolescents had insufficient knowledge, while the posttest results showed that 90% of adolescents had good knowledge after receiving information. The importance of this activity is reflected in the need to form a 'bestie' team to continue providing support to pregnant women. Thus, Remaja Posyandu can be an effective solution to overcome the limited access to maternal health during the pandemic, with the hope of reducing maternal morbidity and mortality.